Decreased resistance to bacterial cold-water disease and excessive inflammatory response in ayu (Plecoglossus altivelis) reared at high water temperature - Kato, Goshi; Nakajima, Hayato; Suzuki, Kyuma; Kanzawa, Yuhei; Nakayasu, Chihaya; Taguchi, Kosei; Kurata, Osamu; Sano, Motohiko (Frontiers in Immunology, 2023)
As most fish species are poikilotherms, their physiological functions, including immune system functions, are strongly affected by environmental water temperature. The ayu, Plecoglossus altivelis, an important fish species for Japanese freshwater fisheries, is usually produced under higher water temperatures than the natural conditions to facilitate rapid growth. However, it has been reported that rearing fish at higher water temperatures inhibits the development of the thymus, suggesting that resistance to infectious diseases is reduced in ayu reared at higher water temperatures. Here, we show that decreased resistance to bacterial cold-water disease and excessive inflammatory responses occurred in ayu reared at 22°C compared with those reared at lower temperatures. Ayu larvae were reared at 12°C, 15°C and 22°C for 77 days and fed 3% of their body weight. Ayu reared at 22°C showed a significantly lower thymus index and higher condition factor than those reared at lower temperatures. Infiltrated leukocytes and many melanin pigments were frequently observed in the adipose tissues and spleens of ayu reared at 22°C, respectively, but not in those reared at 12°C. The gene expression levels of inflammatory cytokines such as IL-1β, IL-8 and TNFα in the spleen were significantly higher in the 22°C group than in the 12°C group. The cumulative survival rate after challenge with Flavobacterium psychrophilum was 51.7%, 40.0% and 13.3% in the 12°C, 15°C and 22°C groups, respectively. Furthermore, ayu reared at different temperatures were vaccinated with formalin-killed cells of F. psychrophilum and challenged with the bacteria. The relative percent survival values of the 15°C and 22°C groups were lower than that of the 12°C group. Moreover, the specific antibody titer of the vaccinated fish was the lowest in the 22°C group and the highest in the 12°C group. These results suggest that rearing the fish under high water temperature causes excessive inflammatory responses similar to metabolic inflammation in human obesity, resulting in a decrease of disease resistance. In addition, thymic involution induced by higher water temperature probably leads the poor response to vaccination. The present study provides insights into the physiological and immunological changes of fish under global warming.